Evaluation of the success and complication rates of endoscopic retrograde cholangiography according to the difficulty of the procedure. Issue 1 (20th November 2022) - Demir, Teyfik; Ustaoglu, Muge
Abstract: Endoscopic retrograde cholangiopancreatography (ERCP), is an invasive procedure with a high complication rate used in the diagnosis and treatment of pancreaticobiliary system diseases. A system that grading the difficulty and complexity of the ERCP procedure has been developed by the American Society of Gastrointestinal Endoscopy (ASGE). The aim of the study is to evaluate the degree of difficulty of ERCP procedures according to the ASGE grading system and its effectiveness in predicting the success and complications of the procedure. A total of 600 patients who underwent ERCP were evaluated retrospectively. Of all ERCP procedures, 5.5% were classified as ASGE 1, 46.8% as ASGE 2, 39% as ASGE 3, and 8.6% as ASGE 4. In all procedures, the successful cannulation rate was 96.3%, the technical success rate was 96%, and the clinical success rate was 94.8%. The procedure's success decreased linearly and the need for repetition increased linearly as the ASGE grade increased ( p  > .05). In terms of complications, there was no statistical difference between ASGE 1–3 and 4. We believe that the ASGE grading system will be useful in clinical practice, particularly for less experienced endoscopists in ERCP procedures. Abstract : A total of 600 patients who underwent ERCP were evaluated retrospectively. 5.5% of ERCP procedures were in ASGE 1, 46.8% were in ASGE 2, 39% were in ASGE 3, and 8.6% were in ASGE 4. As the ASGE grade increased, the success of the procedure decreased linearly and the need for repetition of the procedure increased linearly ( p  > .05).